Effects of physical activity on pain, fatigue, inflammation and cardiovascular risk in rheumatoid arthritis - Wirkijowska, Małgorzata; Wirkijowski, Jakub; Woźniak, Paulina; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Wietrzykowska, Ewa; Śliwińska, Martyna; Wójtowicz, Katarzyna; Walczak, Agata; Sobolewska, Dominika; et al. (Quality in Sport, 2025)
Introduction and aim of the study: The prevalence of rheumatoid arthritis in our society is relatively high. As a result, the number of people requiring some kind of treatment or improvement in quality of life is also increasing day by day. In our study, we aimed to explore the topic of reducing discomfort associated with this condition. We decided to examine the effects of physical activity on individual complaints and systemic symptoms. We summarised the influence of different exercises on pain, fatigue, inflammation, and the cardiovascular system. Materials and methods: The authors conducted an extensive review of articles available in PubMed, Google Scholar, UpToDate, Science Direct, and Cochrane databases. The keywords rheumatoid arthritis, physical activity, quality of life, pain, inflammation, fatigue, and cardiovascular diseases were the basis of the review. Studies published between 2004 and 2024 were included. Results: Most studies emphasized the positive effects of exercise, particularly aerobic and resistance training, on improving the clinical conditions and well-being of patients with rheumatoid arthritis. Nevertheless, the papers with inconsistent results underscored the need to delve further into this topic.